1998
DOI: 10.1038/sj.gt.3300768
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer vectors derived from equine infectious anemia virus

Abstract: Equine infectious anemia virus (EIAV) is a lentivirus in the genes into cultured human cells. In addition, stable helper retrovirus family of viruses. Replication-defective EIAV veccell lines were created by modifying human 293 cells to tors have been constructed that encode bacterial puromyexpress EIAV proteins. Unlike retroviral vectors based on cin-N-acetyl transferase and E. coli ␤-galactosidase. These murine leukemia virus, EIAV lentiviral vectors transduce vectors could be prepared with titers greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(142 citation statements)
references
References 30 publications
2
139
0
1
Order By: Relevance
“…19,20 Cells were grown in DMEM supplemented with 10% fetal calf serum and transfected with plasmid vectors to transiently produce infectious virus particles as previously described. 21 Virus titration was performed on D17 canine cells and human HT1080 cells by seeding cells onto 12-well culture dishes at 8 Â 10 4 cells/well followed by the addition of serially diluted virus. Virus was left on cells for 24 h before removal.…”
Section: Production Of High Titre Equine Infectious Anaemia Virus (Eiav)mentioning
confidence: 99%
“…19,20 Cells were grown in DMEM supplemented with 10% fetal calf serum and transfected with plasmid vectors to transiently produce infectious virus particles as previously described. 21 Virus titration was performed on D17 canine cells and human HT1080 cells by seeding cells onto 12-well culture dishes at 8 Â 10 4 cells/well followed by the addition of serially diluted virus. Virus was left on cells for 24 h before removal.…”
Section: Production Of High Titre Equine Infectious Anaemia Virus (Eiav)mentioning
confidence: 99%
“…22,37 SMART2Z is an EIAV vector expressing the b-galactosidase gene driven by the CMV promoter. It also contains the central polypurine tract from EIAV (cppt) 38 and the WPRE element from the woodchuck hepatitis virus.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, lentiviruses that can infect nondividing cells 18 have been shown to provide more efficient gene transfer and sustained gene expression in vivo. 20,21 MLV-based vectors have been applied by intratracheal, intrahepatic, and intraperitoneal injection to fetal sheep and rats; 18,[22][23][24][25] however, only low levels of transgene expression were observed in all cases. Intraperitoneal vector injection to fetal sheep at 60 days of gestation resulting in marker gene expression in haematopoietic cells until at least 40 months was attributed both to the expression from an integrating vector system as well as to the induction of immune-tolerance against the transgenic protein.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive body of knowledge that has been generated on this virus has allowed researchers to reengineer it as a gene vector. HIV-1 remains the best studied vector (Lever et al 2004), although recent work has revealed the potential of HIV-2 (Sadaie et al 1998) SIV (Schnell et al 2000;Stitz et al 2001), EIAV (equine infectious anemia virus) (Olsen 1998;Mitrophanous et al 1999;Ikeda et al 2003) 2002; Loewen et al 2003) and BIV (bovine immunodeficiency virus) (Takahashi et al 2002) as vectors.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%